Skill Dispersion and Firm Productivity: An Analysis with Employer‐Employee Matched Data - Iranzo, Susana; Schivardi, Fabiano; Tosetti, Elisa (Journal of Labor Economics, 2008)
We study the relation between workers’ skill dispersion and firm productivity using a unique data set of Italian manufacturing firms with individual records on all their workers. Our measure of skill is the individual worker’s effect from a wage equation. We find that a firm’s productivity is positively related to skill dispersion within occupational status groups (production and nonproduction workers) and negatively related to skill dispersion between these groups. Consistently, most of the overall skill dispersion is within and not between firms. These findings are consistent with some recent hierarchical models of the firms’ organizational structure.